Surfactant Protein D Facilitates Cryptococcus neoformans Infection - Geunes-Boyer, Scarlett (American Society for Microbiology, 2012)
Concurrent with the global escalation of the AIDS pandemic, cryptococcal infections are increasing and are of significant medical importance. Furthermore, Cryptococcus neoformans has become a primary human pathogen, causing infection in seemingly healthy individuals. Although numerous studies have elucidated the virulence properties of C. neoformans, less is understood regarding lung host immune factors during early stages of fungal infection. Based on our previous studies documenting that pulmonary surfactant protein D (SP-D) protects C. neoformans cells against macrophage-mediated defense mechanisms in vitro (S. Geunes-Boyer et al., Infect. Immun. 77:2783–2794, 2009), we postulated that SP-D would facilitate fungal infection in vivo. To test this hypothesis, we examined the role of SP-D in response to C. neoformans using SP-D(−/−) mice. Here, we demonstrate that mice lacking SP-D were partially protected during C. neoformans infection; they displayed a longer mean time to death and decreased fungal burden at several time points postinfection than wild-type mice. This effect was reversed by the administration of exogenous SP-D. Furthermore, we show that SP-D bound to the surface of the yeast cells and protected the pathogenic microbes against macrophage-mediated defense mechanisms and hydrogen peroxide (H(2)O(2))-induced oxidative stress in vitro and in vivo. These findings indicate that C. neoformans is capable of coopting host SP-D to increase host susceptibility to the yeast. This study establishes a new paradigm for the role played by SP-D during host responses to C. neoformans and consequently imparts insight into potential future preventive and/or treatment strategies for cryptococcosis.